2023
DOI: 10.3390/smartcities6020040
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain in the Construction Industry between 2016 and 2022: A Review, Bibliometric, and Network Analysis

Abstract: In recent years, applications of Blockchain technology (BCT) have been progressing at a galloping rate in miscellaneous fields, such as finance, education, travel, healthcare, and insurance. However, BCT has gained much popularity in the construction industry, especially in developed nations worldwide, as it can solve real-world problems, including poor payments, inadequate cooperation and collaboration, inappropriate data sharing among stakeholders, and poor efficiency. The current research employs a bibliome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 118 publications
0
1
0
Order By: Relevance
“…Each checklist item was accompanied by an "explanation and elaboration" section, providing the rationale and additional guidance, along with exemplars to facilitate comprehensive reporting. The approach employed in this review aims to elucidate the relationships among authors, regions, keywords, and journal citations, while also providing a concise evaluation of the current state-of-the-art research fields and potential emerging trends [108].…”
Section: Methodsmentioning
confidence: 99%
“…Each checklist item was accompanied by an "explanation and elaboration" section, providing the rationale and additional guidance, along with exemplars to facilitate comprehensive reporting. The approach employed in this review aims to elucidate the relationships among authors, regions, keywords, and journal citations, while also providing a concise evaluation of the current state-of-the-art research fields and potential emerging trends [108].…”
Section: Methodsmentioning
confidence: 99%
“…The "trustless" concept in BC means that trust is not required between parties for transactions to be securely executed; BC itself provides the necessary security and verification mechanisms, ensuring the integrity and reliability of transactions. [34].…”
Section: Blockchainmentioning
confidence: 99%
“…These include, for instance, literature reviews [8,[14][15][16][17][18], case studies [19][20][21][22], descriptive analyses [23][24][25][26], and bibliometric and content analyses [27][28][29][30]. Moreover, it is noteworthy to highlight that while some studies focus exclusively on qualitative research [31][32][33], others adopt quantitative methods, using statistical analyses to review the literature without qualitative techniques like interviews or thematic content, as highlighted in Shishehgarkhaneh et al [34] and Ameyaw et al [35]. Meanwhile, a third group integrates both approaches, notably [36][37][38][39][40], highlighting the methodological diversity in the field.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that blockchain enables unprecedented visibility at each step of the food supply chain, helps increase transaction transparency, food safety, and quality, and reduces food fraud and waste. Milad B. et al [28] identified notable publications, conferences, significant authors, nations, organizations, and funding organizations. Their research indicates that the primary research topics include blockchain in the construction industry, supply chain management, smart contracts, sustainability, building information modeling (BIM), the Internet of Things (IoT), and energy efficiency.…”
Section: Blockchain and Its Application In Property Rights Transactionsmentioning
confidence: 99%